Synergy of Fiqh and Sufism from the Perspective of Abu Bakr al-Dimyati in the Book Kifayah al-Atqiya' wa Minhaj al-Asfiya' - Maimunah, Hanik Nur; Rizqiyah, Afi; Darwati, Aan (LPPM Institut Pendidikan Nusantara Global, 2025)
Fiqh and Sufism are two branches of religious science with different orientations. Fiqh and Sufism have experienced a dichotomy because Sufism is oriented towards esoteric issues, while fiqh is oriented towards exoteric issues. Therefore, this study examines the synergy of fiqh and Sufism from the perspective of Abu Bakar al-Dimyati in his book entitled Kifayah al-Atqiya' wa Minhaj al-Asfiya' . This book contains a discussion of the morality of Sufis in taking the path to get closer to Allah SWT. So this study aims to analyze the synergy of Fiqh and Sufism Perspective of Abu Bakar al-Dimyati in the Book of Kifayah al-Atqiya' wa Minhaj al-Asfiya' . This type of research is library research, with a qualitative approach. The data was collected using documentation techniques, then analyzed using content analysis techniques. The main data source of this research is the book of Kifayah al-Atqiya' wa Minhaj al-Asfiya' with secondary data sources of relevant books and articles. The results showed the need for synergy of fiqh and Sufism. Fiqh as one of the sciences that contains learning of Islamic law is the initial step of a servant's journey in getting closer to Allah Swt which is the scope of Sufism. So that fiqh and Sufism cannot be separated, in fact they must be synergized with each other by every Muslim who seeks to get closer to Allah SWT. This research is expected to be able to broaden the insight of Muslims in exploring their role as servants and caliphs by adhering to sharia and Sufi morals.